Zgornji Jadran - Bufon, Milan (Annales. Series historia et sociologia, 2009)
When considering the Upper Adriatic, the meeting point of three countries: Italy, Slovenia and Croatia at this point in time, an important fact needs to be acknowledged - the historic fate of this area has basically been determined by the relationship between the ethnical and political border. In this particular area the two borders normally do not coincide and had been perpendicular or parallel to one another in different historical periods. Several contradictory tendencies towards the adapting of social structure and social systems to the current political organization of space can be discerned in the process of politically-geographical transformations in the area discussed. On one hand, particularly on the local scale, there are tendencies to normalize and functionally organize the trans-border communication and socially-cultural and socially-economic structures. On the other hand, particularly on the scale of state relations, there are tendencies to preserve the state of tension and the air of restriction around the border. This has lead to a considerable discrepancy between the intensity of functional trans-border connections, which have gradually developed between the two sides, and the scarcity and reservedness of institutional trans-border associations, which have only started to develop after the Treaty of Osimo was signed in 1975. The fact that "the spirit of Osimo" did not develop and strengthen after the proclamation of independence of Slovenia in 1991, its entry into the EU in 2004 and the acceptance among the Schengen countries in 2007 is rather unusual. Despite the existence of intensive and functional trans-border associations of the population residing near the border, the neighboring countries in the area of Upper Adriatic did not manage to devise any new initiatives concerning institutional integration. Furthermore, along with the break in communication between Slovenia and Italy, a deterioration of relations between Slovenia and Croatia occurred because of unresolved petty disputes concerning the border. However, the rather unfavorable state of relations between the states is not reflected in the actual situation in the field. The research performed so far indicates that there is a quite distinct trans-border interdependence of the population residing near the border. Nevertheless, the current politically-geographical transformations have generated certain differences between the Slovene-Italian border and the Slovene-Croatian border, particularly in the scope of lowering expectations with respect to further development of trans-border relations and lower level of functional trans-border association characterizing the western border sector of the Slovene-Croatian border when compared to the Istrian-Karstic border section of the Slovene-Italian border. This fact reflects the negative effects of transformations in this formerly unified or correlated socially-geographical area and the consequential differentiation of border sectors regardless of the relatively high level of socially-cultural affinity, which still characteriyes both border regions. This provides grounds for understanding the simultaneous occurrence of tendencies towards social and spatial divergence, characteriying the relationship of past and present-day state-oriented politicians in relation to their neighboring countries, and tendencies towards social and spatial convergence, originating primarily from the socially-cultural affinity and socially-economic interdependence of the population residing near the border. The above demonstrates that border regions should be granted an institutional and legal status that will enable the population of these regions to successfully resolve their own developmental problems while considering the complex social structure of the Upper Adriatic in the perspective of renewing or improving the spatial integration or reducing the level of potential conflict. Developmental history and the current social structure suggest that this region is indeed much easier to interconnect than to divide
Keywords: Croatia; Hrvaška; Istra; Istria; Italija; Italy; obmejna območja; politična geografija; severni Jadran; Slovenia; Slovenija